Clinical efficacy of general anesthesia versus local anesthesia for percutaneous transforaminal endoscopic discectomy - Wu, Zhihua; He, Jiahui; Cheng, Huantong; Lin, Shaohao; Zhang, Peng; Liang, De; Jiang, Xiaobing; Cui, Jianchao (Frontiers in Surgery, 2023)
Objective: Local anesthesia(LA) is recommended for percutaneous transforaminal endoscopic discectomy(PTED), but satisfactory pain management is not mostly achieved.The goal of this study was to examine the clinical efficacy of PTED for lumbar disc herniation when performed under local anaesthetic versus general anesthesia (GA). Methods: From August 2018 to August 2020, the clinical data of 108 patients treated with PTED were retrospectively evaluated and separated into two groups: LA and GA based on the anesthesia method. General information and clinical outcomes of patients were included. Visual analog scale (VAS) and Oswestry disability index (ODI) were recorded before operation, 1 week after operation, and 1 year after operation. In addition, VAS for back pain and leg pain on the second postoperative day were also recorded. Results: We divided the patients into two groups: 72 in LA and 36 in GA . There were no significant differences in gender, age, course of disease, body mass index, surgical segment, duration of operation, intraoperative bleeding, time of fluoroscopy, length of hospital stay, total hospitalization cost reoperation, surgical satisfaction, Macnab satisfaction, complications, preoperative and 1 year postoperatively VAS for back pain and leg pain and ODI,VAS for leg pain on the second day and 1 week postoperatively between the two groups (P＞0.05). VAS for back pain in GA group on the second day postoperatively, as well as the VAS for back pain and ODI at one week postoperatively, were better than those in LA group. (P<0.05). However, the total hospitalization cost in LA group was significantly lower than that in GA group (P<0.05). Further analysis of different ages in the two groups showed that there were significant differences in the VAS for back pain on the second day postoperatively and ODI at 1 week postoperatively in the middle-aged group (45≤Y≤59), as well as the VAS for back pain on the second day postoperatively in the senior group (Y≥60) (P<0.05). However, there were no significant difference among other groups (P>0.05). Conclusion: Long-term outcomes were similar for both PTED under LA and GA, while GA group had better short-term outcomes, especially in middle-aged and elderly patients.